Unpacking Mathematics for Teaching: A Study of Preservice Elementary Teachers' Evolving Mathematical Understandings and Beliefs - Ann Kajander (University of Windsor, 2007)
This study examined the mathematical understandings and beliefs held by preservice elementary teachers in a mathematics methods course taken as part of a one year teacher certification program, and re-examined these characteristics at the end of the course. The notion of 'understanding mathematics for teaching' was examined in a way that might begin to support the work of mathematics educators working with such preservice teacher candidates. Preservice teacher beliefs about what is important in mathematics learning and therefore the teaching of it are examined along with mathematics understanding at both procedural and conceptual levels. The goal is to shed some light on how initial understanding and beliefs about mathematics teaching co-exist, and how these might develop during a preservice teacher education program. A preliminary model designed to promote participant self-reflection is suggested.